Analisis Intensitas Penerangan dan Penggunaan Energi Listrik di Laboratorium Komputer Sekolah Dasar Negeri 150 Pekanbaru - Atmam Atmam; Zulfahri Zulfahri (UIN Sultan Syarif Kasim Riau, 2015)
The intensity of illumination on the computer laboratory for basic educational institutions such as elementary schools, must have a good quality and quantity as well as the consumption of electrical energy efficiently. If the illumination intensity of a space laboratory is not met, then it will lead to discomfort for elementary school students in carrying out the computer lab. For the quantity of lighting a computer lab space, mostly resulting from the use of lighting lamp. Excessive use of lighting for computer labs will affect the wasteful use of electric energy. To view these conditions, the research conducted by the measurement method of light intensity at the working point and by the SNI 16-7062-2004 standards. From the results of this study gained an average light intensity in the computer lab room of Elementary School no 150 of Pekanbaru for each working point of 171 lux, so that the illumination intensity is still low and according to standard measurements SNI 16-7062-2004 intensity values obtained by an average of 122 lux and it does not meet the standards. The consumption of electrical energy to meet the illumination intensity of the computer lab when using this lamp type of CFL 35W/2100 lm, the electrical energy consumption of 5.88 kWh and when using this lamp type of CFL 58W/3500 lm, the electrical energy consumption of 5.57 kWh.Keywords: Electrical Energy, Intensity Lighting,